Analisis Pengaruh Coaching dan Komunikasi terhadap Employee Engagement melalui Loyalitas pada PT. Bank X (Persero) Tbk., Kantor Regional X Sulawesi dan Maluku - Widiawaty Mochtar; Rosnaini Daga; Abdul Samad A (Movere Journal, 2025)
This research aims to determine and analyze the Influence of Coaching and Communication variables on Employee Engagement through Loyalty at PT. Bank X (Persero) Tbk., Regional Office X Sulawesi and Maluku. The analytical tool used in this research is data analysis using SEM-PLS. The population in this study were all employees of PT. Bank X (Persero) Tbk., Regional Office X Sulawesi and Maluku with 2,140 employees. Using purposive sampling technique, so the sample used is all permanent employees of PT. Bank X (Persero) Tbk., Regional X Office with a certain level, namely 119 employees. Research results show that : (1) Coaching has a positive and significant effect on Loyalty at PT. Bank X (Persero) Tbk., Regional X Office, (2) Communication has a positive and significant effect on Loyalty at PT. Bank X (Persero) Tbk., Regional X Office, (3) Coaching has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Region X Office, (4) Communication has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Regional X Office (5) Loyalty has a positive and significant effect on Employee Engagement at PT. Bank X (Persero) Tbk., Regional X Office, (6) Coaching has a positive and significant effect on Employee Engagement through Loyalty to PT. Bank X (Persero) Tbk., Region X Office (7) Communication has a positive and significant effect on Employee Engagement through Loyalty to PT. Bank X (Persero) Tbk., Regional X Office.